In-situ bio-stimulation for enhanced biological methane production and its effect on the microbiome of CBM wells in Raniganj block, India - Chawla, Mansi; Lavania, Meeta; Sahu, Nishi; Banerjee, Dipanjana; Singh, Nimmi; Lal, Banwari (Frontiers in Bioengineering and Biotechnology, 2025)
Microbially enhanced coalbed methane production (MeCBM) is a way towards translation of the recent momentum of the high demand for renewable energy into operational capacity. The present study demonstrates the enhancement of biogenic methane in coalbed methane (CBM) wells of an Indian coal reservoir via in-situ biostimulation. A laboratory-scale strategy was previously developed to understand and enhance the microbial processes for the bioconversion of coal to methane before transferring it to the field. The quantitative measurement of gas production after the industrial-scale microbial stimulation job carried out at the EOGEPL Raniganj block indicated upto a four-fold enhancement in methane production, with the best results observed in Well-B, from a baseline production of 117.04 standard cubic meters per day (scmd) to 461.38 scmd, followed by Well-E, with an increase from 210.93 scmd to 385.19 scmd, and Well-C, with an increase from 514.22 scmd to 670.22 scmd. Molecular and isotopic compositions of the gases collected by post-nutrient injection have been studied and the results indicate the occurrence of secondary microbial gas. The 16s rRNA amplicon sequencing analysis of formation water samples post-nutrient injection, and its comparison with previously published pre-injection microbial community analysis gives an insight into the impact of the microbial stimulation on the indigenous microbiome of the CBM wells. The present study provides a framework for understanding the effects of in-situ biostimulation via nutrient amendment in a coal reservoir. Further, the findings of the study will help to implement methane enhancement strategy via biostimulation on a wider range of coal fields to enhance its commercial potential.